(untitled) (Asian Journal of Pharmaceutics (AJP), 2015)
PEGylation involves chemically linking polyethylene glycol (PEG) to the therapeutic molecule for the purpose of enhancing its therapeutic value. PEG conjugates of the anticancer agent have been designed to enhance the water solubility andÂ plasma halfâ€life of the drug. Biodegradable polymeric micelles are used for drug delivery to the site of the tumor, as theyÂ possess thermodynamic stability, ability to encapsulate and solubilize a hydrophobic guest molecule, biodegradability, as well asÂ size and surface characteristics that facilitate rapid clearance by the reticuloendothelial system.The prepared ester and amide conjugates of PEG with the drug were lyophilized and characterized. The lyophilized formulations were evaluated for drug loading, drug release, hemolytic toxicity, and stability. PEG was found to solubilize methotrexate (MTX) by forming micelles in the nanometric range. This particle size was considered effective for passive targeting of tumors. Drug loading capacity of the micelles was found to increase with an increase in the amount of MTXâ€PEG conjugate. The rate of drug release from amide derivative of MTXâ€PEG conjugate was slower when compared to ester derivative of MTXâ€PEG conjugate. Prepared MTXâ€PEG conjugate was found to be less hemolytic than the plain drug. The formulation showed maximum stability and minimum drug leakage at 0Â°C. The ester and amide derivatives of MTX with PEG alter the hydrophobicity of the conjugate, thereby modifying micellar stability and controlling drug release. Based on preliminary results, we can conclude that PEGylation of MTX substantially enhances its aqueous solubility. Due to small size, higher solubility, simple sterilization, and controlled release of the drug, polymeric micelles seem to mimic an ideal carrier for poorly water soluble drugs. Key words: Methotrexateâ€polyethylene glycol conjugates, PEGylation, polymeric micelles